Flight activity of Sitophilus oryzae (L) and Sitophilus zeamais Motsch (Coleoptera: Curculionidae) and its relationship with susceptibility to insecticides - Vásquez-Castro,Javier A (2009)
Insect-pest mobility can influence insect susceptibility to the insecticides used to control them. The objective of this work was to evaluate the flight activity of Sitophilus oryzae (L) and Sitophilus zeamais Motsch populations reared on corn and wheat grains, and its relationship with insecticide susceptibility. Unsexed adult insects with ages between 10 and 20 days were placed on a plastic tray. A 40-watt incandescent light bulb was positioned at a 50 cm height relative to the tray. Flight activity was evaluated during 30 min. In the LC50 estimation bioassays, the insects were exposed to dry residues of the organophosphorus insecticide fenitrothion and of the pyrethroid insecticide esfenvalerate on the internal surface of glass vials. Mortality was evaluated 24h after installation of the experiments. Sitophilus zeamais showed greater flight activity when compared with S.oryzae; likewise, insects reared on corn had greater flight activity than those reared on wheat. Sitophilus oryzae was less susceptible to the insecticides studied than S. zeamais. Adults reared on wheat were more susceptible to the insecticides than those reared on corn. This study demonstrates that the lower flight activity of S. oryzae is related to its greater tolerance to insecticides.